2005
DOI: 10.1093/nar/gki964
|View full text |Cite
|
Sign up to set email alerts
|

Human Bex2 interacts with LMO2 and regulates the transcriptional activity of a novel DNA-binding complex

Abstract: Human Bex2 (brain expressed X-linked, hBex2) is highly expressed in the embryonic brain, but its function remains unknown. We have identified that LMO2, a LIM-domain containing transcriptional factor, specifically interacts with hBex2 but not with mouse Bex1 and Bex2. The interaction was confirmed both by pull-down with GST-hBex2 and by coimmunoprecipitation assays in vivo. Using electrophoretic mobility shift assay, we have demonstrated the physical interaction of hBex2 and LMO2 as part of a DNA-binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…We have shown that on the PC1/3 promoter STAT3 and Nhlh2 interact as a heterodimer to mediate leptinstimulated PC1/3 expression. This is a novel mechanism for Nhlh2, which has previously been shown to interact with LMO2 or LMO3 at the E-box motif CAGCTG (29,30). Our results identify a new binding partner for Nhlh2 as well as a new E-box binding site of interaction (CAAATG).…”
Section: Discussionmentioning
confidence: 53%
“…We have shown that on the PC1/3 promoter STAT3 and Nhlh2 interact as a heterodimer to mediate leptinstimulated PC1/3 expression. This is a novel mechanism for Nhlh2, which has previously been shown to interact with LMO2 or LMO3 at the E-box motif CAGCTG (29,30). Our results identify a new binding partner for Nhlh2 as well as a new E-box binding site of interaction (CAAATG).…”
Section: Discussionmentioning
confidence: 53%
“…Human BEX2 was identified in fetal brain and a role in embryonic development has been suggested [24]. Expression was upregulated in MLL mutant AML cell lines compared to MLL wild-type AML cell lines suggesting a role in this particular type of hematological cancers.…”
Section: Bex Genes and Proteinsmentioning
confidence: 99%
“…Furthermore, mice deficient of BEX2 were viable and fertile under normal growth conditions and did not show any obvious phenotypic abnormalities [37]. Although BEX2 is apparently not involved in liver development, another study suggested that human BEX2, but not murine BEX1 or BEX2, associates with LIM-domain containing transcriptional factor (LMO2) [24], leading to enhancement of NSCL2-dependent transcriptional activity which is required for embryonal development.…”
Section: The Role Of Bex Proteins In Normal Cellsmentioning
confidence: 99%
“…13 Unlike many other zinc fingers, the primary function of LIM domains is not to bind DNA, but to mediate interactions with other proteins. 14 LMO2 has been found to interact directly with a number of proteins including Tal1/SCL, GATA-1 and -2, 15 AF6, 16 retinoblastoma-binding protein 2, 17 Elf-2, 18 the neuronal proteins Bex2 and NSCL2, 19 and LIM domain-binding protein 1 (Ldb1/CLIM2/NLI). [20][21][22] LMO2 also participates in a number of multiprotein complexes that can localize to bipartite DNA sequences.…”
Section: Introductionmentioning
confidence: 99%